Formation of media competence based on organization of project activities of future teachers within blended learning - Galustyan, Olga V.; Vlasyuk, Irina V.; Zhirkova, Galina P.; Gamisonija, Saida S.; Zhang, Jingwei; Liu, Siqi (Intelektual Pustaka Media Utama, 2025)
The article is devoted to the problem of formation of media competence which is based on organization of project activities of future teachers within blended learning. Rapid development of digital technologies, expansion of wide public access to the content of various types (professional, educational, and entertainment) leads to the attraction of young people to social networks and Internet media resources. Application of modern media in education makes it possible to prepare highly qualified teachers who can solve professional problems effectively. Thus, the role of developing media competence of future teachers in the information society is increasing. The presented paper reveals the process formation of media competence based on organization of project activities of future teachers within blended learning which include creating educational media products. The results of experimental work of formation of media competence based on organization of project activities of future teachers within blended learning in control and experimental groups reveal that in the experimental group the level of media competence of future teachers is higher than in the control group, that proves the effectiveness of experimental work.